Ketergantungan Petani Sawit terhadap Hasil Panen dalam Pembiayaan Pendidikan Anak di Desa Danau Lancang - Dewi Astarina Sirait; R.M Riadi; Brilliant Asmit (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze the influence between palm oil plantation income on the allocation of child education financing. This study is a quantitative research using descriptive methods supported by literature study. The population used in this study was parents whose main income is from the palm oil sector, children who are still in education, live settled in Lancang Village, specifically Mandau road and own palm plantation. The data collection method used a survey and questionnaire distributed luring to 100 parents. The sampling technique was conducted using purposive sampling. The data analyzes used in this study were descriptive analysis and simple linear regression analysis. The results of the study indicate that there is a positive influence of between oil palm plantation income on the allocation of financing oil palm plantation owners’ children’s education.